Examining ESL pre-service teachers’ perceived roles and perceived responsibilities of teaching writing skills - Mohd Amir Izuddin, Mohamad Ghazali; Zuraina, Ali; A.A.A, Rahim (2022)
Practicum is a crucial assessment component for English as Second Language (ESL) pre-service teachers (PSTs). However, evidence suggested that they encountered many challenges, including the lack of experience and skill to teach language skills, mainly writing skills. Significantly, this paper intends to explore the perceived roles and perceived responsibilities of PSTs when conducting writing classes during their practicum stint. This study employed a qualitative approach involving five (5) ESL PSTs as its samples. A focus group interview was carried out, and the data was analyzed thematically. Three (3) themes were generated, suggesting specific roles and responsibilities that a PST must carry out for each stage, i.e., prewriting, while-writing, and postwriting stages. Overall, these findings underscore the necessity of developing a framework for ESL PSTs' roles and responsibilities to guide them when teaching writing skills, eventually improving their teaching performance during practicum.